REGULARIZATION OF THE SOLUTION OF THE CAUCHY PROBLEM FOR A SYSTEM OF EQUATIONS OF ELASTICITY THEORY IN AN INFINITE DOMAIN (International journal of artificial intelligence, 2026)
The paper discusses continuation of a solution of the elasticity system in a domain from its values and the values of its stresses on part of the boundary, i.e. the Cauchy problem for the Lame system.